Histórias contadas, histórias vividas: a constituição de identidades de professores/as negro/as - Carneiro, Tania Maria Cesar (2014)
The research aim at the analysis of the constitution of identities of the racial-ethnic relationships as well as the discursive practices in narratives of black teachers who work in the fundamental teaching of public schools in the municipalities of Mamanguape and Rio Tinto, located in the Mamanguape Valley region, places where units of the UFPB Campus IV operate. To do so, it problematizes educators narratives of the school units generated like linguistic materiality specifically produced for this investigation. Thus, the guiding issue adoption is: how the sense effects expressing focuses of resistance are translated in the discursive-linguistic materiality of the life narratives of black teachers when these – whilst involved in the task of getting rid of stereotyping and stigmatizing identities – look for its change in the relation themselves, in an ethical attitude? It also aims at analyzing the process of constitution of identities in linguistic-discursive sequences that compose biographical scripts and narratives of black teachers as from the relationship between liberty practices and truth discourses as regards the school trajectory, family co-existence, social mobility, , affect-marital arrangements and social The research is inserted in the area of Applied Linguistics and adopts the concept of language as a social practice (MOITA LOPES, 2006). The investigation affiliates notions of the French Discourse Analysis (DA) on discourse and inter-discourse and foucaultian theorizations about the discursive formation and practice and identity constitution in social institutions. The analyzed discursiveness showed that teachers adopt the ego technologies as a form of resistance before discriminating and excluding practices, when constituting their identities.